Gestão ambiental na educação: um estudo sobre fatores que afetam o comportamento ambiental de professores do ensino médio, na cidade de Floriano-PI - Diniz, Marcos Antonio Ribeiro (2006)
The present work sets out environmental issues in educational field. The aim of this research was to investigate the factors capable to influence the environmental behavior of the teachers in High school of the public school in Floriano, state of Piaui. For this, the methodology utilized an explanatory and descriptive search like a survey; questionnaires were applied with open and close questions establishing shifts that made up the following aspects; knowledge, behavior, responsibility, participation and trait of the teachers. The statistic techniques to analyze the data were descriptive analysis and analysis of multiple regression. The results reveal that teachers care about the real surrounding problems and believe that the school must develop ambient activities to stir the consciousness, it is important to the environmental improvement of the city. However, the results point out that are developed little activities related to theme concerned, besides the level of ambient consciousness given to the students are median. It was observed that teachers have little knowledge about theme like Agenda 21 and ISO14000. After identifying some factors of environmental knowledge, it was showed recommendations. The Agenda 21 recognizes in the educational field a mean of popular consciousness; the school should develop an education according to national policy of the environmental education